2023
DOI: 10.1002/cphc.202200642
|View full text |Cite
|
Sign up to set email alerts
|

DFT‐based Machine Learning for Ensemble Effect of Pd@Au Electrocatalysts on CO2 Reduction Reaction

Abstract: The ensemble effect due to variation of Pd content in Pd−Au alloys have been widely investigated for several important reactions, including CO2 reduction reaction (CO2RR), however, identifying the stable Pd arrangements on the alloyed surface and picking out the active sites are still challenging. Here we use a density functional theory (DFT) based machine‐learning (ML) approach to efficiently find the low‐energy configurations of Pd−Au(111) surface alloys and the potentially active sites for CO2RR, fully cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…[44][45][46] Among the most relevant local chemical descriptors proposed to date, those focused on correlating the nearest neighboring surface atoms to the adsorption site have gained signicant attention. These descriptors include the average of elemental properties, 47 atom-specic ngerprints derived from elemental properties, 48,49 and use ML models based on neural networks, [50][51][52] or graph neural networks. [53][54][55][56] However, these descriptors have difficulties adapting to other adsorbates or ML-based model architectures, hindering their transferability to other systems.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] Among the most relevant local chemical descriptors proposed to date, those focused on correlating the nearest neighboring surface atoms to the adsorption site have gained signicant attention. These descriptors include the average of elemental properties, 47 atom-specic ngerprints derived from elemental properties, 48,49 and use ML models based on neural networks, [50][51][52] or graph neural networks. [53][54][55][56] However, these descriptors have difficulties adapting to other adsorbates or ML-based model architectures, hindering their transferability to other systems.…”
Section: Introductionmentioning
confidence: 99%
“…28 Liu investigated the adsorption energies on binary alloy surfaces of Pd n Au 16−n alloyed surface with different Pd content (n = 1-16) by ML prediction and concluded that the isolated Pd top sites surrounded by Au atoms are stable adsorption sites. 29 Nayak et al predicted adsorption energies of H, O, N, OH, NO, and CO on fcc(111) surface top sites of 25 different transition metals including Ir, Pt, and Au with an average root-mean-square error (RMSE) of about 0.4 eV by random forest regression. 30 Prediction of adsorption energies on metal and alloy surfaces was also reported using the XGBoost regression, 31 articial neural network algorithm, 32,33 random forest, 34 and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…the entire topmost layer of the metal was replaced by another metal element, while the actual conguration of alloys in real catalysts could be much more complex. 29 In this study, we directly exploit the adsorption energies of CO 2 and CO on surfaces of a wide range of binary alloys using ML methods without any assumptions of linearity, i.e. we do not assume the adsorption energy on alloys to be a linear combination of adsorption affinity on its two component metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd-based electrocatalysts are well-known for their outstanding CO Oxid activity, due to their ability to enhance the activation/dissociation of reactants (CO + O 2 ) under low applied potential and weaken the adsorption of carbonaceous intermediates; however, the earth-scarcity and high-cost of Pd conspired the commercial utilization. , This issue could be vanquished via reducing amount of Pd, by alloying Pd with inexpensive and earth-abundant metals (i.e., Ni, Mn, Cu, Fe, and Co) and/or using supports (i.e., carbon and metal oxide), which reduce the loading of Pd usage and enhance the CO Oxid activity . Mainly, alloying effect generates a kind of electronic interaction (i.e., synergism and strain), which endows the activation/dissociation of reactants, eases H 2 O dissociation to release oxygenated species for accelerating the CO Oxid kinetics, and facilitates the desorption of product (i.e., CO 2 ) under low potential . For instance, Pd nanocrystals supported on Co–ZIF-derived hierarchical porous carbon nanosheets (Pd/ZIF-67/C) exhibited electrocatalytic CO Oxid that outperformed commercial Pd/C by 4.0 times in HClO 4 medium, due to the interaction of Pd with ZIF-67/C, porous structure of ZIF-67/C and abundance active sites of Co–N x .…”
Section: Introductionmentioning
confidence: 99%